2007
DOI: 10.1182/blood-2006-07-036889
|View full text |Cite
|
Sign up to set email alerts
|

Mast cells are crucial for early inflammation, migration of Langerhans cells, and CTL responses following topical application of TLR7 ligand in mice

Abstract: Until recently, IgE-activated mast cells have been regarded merely as effector cells of adaptive immune responses, involved in allergic reactions and mucosal immunity to parasites. Herein, we report that murine dermal mast cells, activated by local administration of a cream containing the synthetic TLR7 ligand imiquimod, are essential to initiate an early inflammatory reaction. The mast-cell-derived cytokines TNF-␣ and IL-1␤ play an important role in this process. Furthermore, TLR7-activated mast cells are als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
108
1
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 103 publications
(115 citation statements)
references
References 47 publications
(76 reference statements)
3
108
1
3
Order By: Relevance
“…Administration of poly(I:C) or R848 in addition to allergen have both been described to induce allergen-specific CD8 + T cells and Th1 cytokine production when applied via the skin (41,42). However, in the current model only administration of TLR3 ligand into the lung resulted in an inflammatory response with increased numbers of lymphocytes and eosinophils in the airways and increased expression of cytokines and chemokines.…”
Section: Discussioncontrasting
confidence: 41%
“…Administration of poly(I:C) or R848 in addition to allergen have both been described to induce allergen-specific CD8 + T cells and Th1 cytokine production when applied via the skin (41,42). However, in the current model only administration of TLR3 ligand into the lung resulted in an inflammatory response with increased numbers of lymphocytes and eosinophils in the airways and increased expression of cytokines and chemokines.…”
Section: Discussioncontrasting
confidence: 41%
“…Furthermore, dermal mast cells were shown to be essential in the imiquimod-induced immune response. Both early cutaneous inflammation and migration of Langerhans cells were promoted by TLR7-activated mast cells, with mast cell-derived TNF-␣ and IL-1 as the essential mediators [55].…”
Section: Dcs and B Cellsmentioning
confidence: 99%
“…Mast cells have a regulatory role in the development of IMQinduced dermatitis in mice-in particular, in the initiation phase of dermatitis-via regulation of tumor necrosis factor-α and IL-1β (Heib et al, 2007). In addition, we have previously shown that Clock mutation affects IgE-mediated mast cell responses (Nakamura et al, 2011(Nakamura et al, , 2014.…”
Section: Mast Cells Have a Marginal Role In Imq-induced Dermatitis Inmentioning
confidence: 99%